Development of a Liquid Scintillator Using Water for a Next Generation Neutrino Experiment - Sun Heang So; Kyung Kwang Joo; Ba Ro Kim; Bong Keon Kim; Seung Chan Kim; Chang Dong Shin; In Sung Yeo (Advances in High Energy Physics)
A feasibility study on a new type of liquid scintillator based on water has been performed. Mainly due to the differences in polarities between water and oil, organic solvents are not mixed in water. In order to make a liquid scintillator based on water, a surfactant that contains hydrophilic and hydrophobic groups is used. The surfactant keeps water and organic solvents apart in solution. Good physical and optical parameters and long-term stability are required to use liquid scintillator based on water in massive detector for the next generation neutrino experiments. In this paper, we report the characteristics and the possibility of liquid scintillators using water with various new surfactants.